The Prognostic significance of the tumor budding and tumor-infiltrating lymphocytes in survival of hepatocellular carcinoma patients - Shafiq, Ahmed Mahran; Taha, Noura Ali; Zaky, Amen Hamdy; Mohammed, Abdallah Hedia; Omran, Ola M.; Abozaid, Lobaina; Ahmed, Hagir H. T.; Ameen, Mahmoud Gamal (International Journal of Health Sciences, 2024)
Objective: In spite of great advance in the management of hepatocellular carcinoma (HCC), the prognostic factors are still obviously not understood. The role of tumor budding (TB) and tumor-infiltrating lymphocytes (TILs) in HCC as pathological parameters affecting prognosis stands principally unknown. Methods: Seventy-four surgical resection pathology specimens of HCC patients were used. Assessment of TB and TILs were performed using hematoxylineosin-stained slides. Follow-up data were collected over a 5-year period to determine disease-free survival rates, overall survival (OS) rates, and how they related to TB, TILs, and other clinicopathological factors. Results: There was a significant statistical association between high-grade TB and lymphovascular embolization (LVE), tumor necrosis, and grade of HCC with P = 0.003, 0.036, and 0.017, respectively. The positive TILs group showed a statistically significant correlation with histological grade, LVE, and serum alphafetoprotein (AFP) level with P = 0.002, 0.006, and 0.043, respectively. Multivariate analysis using the Cox proportional hazard model revealed that TILs are not an independent pathological factor for disease-free and OS, although TB is an independent pathological factor for both. Conclusions: In all HCC patients, TB was seen, and there was a significant link between the grade of the HCC and the presence of tumor necrosis, LVE, and high-grade TB. The majority (92%) of HCC patients had TILs, and there was a strong relationship between the histological grade, LVE, and serum AFP level. While TILs show variation of the immunologic reaction to the tumor, TB tends to suggest a hostile biologic nature and a bad prognosis.